Power Relations and Social Mix in Metropolitan Neighbourhoods in North America and Europe: Moving Beyond Gentrification?. (28th April 2014) - Bridge, Gary; Butler, Tim; Le Galès, Patrick
Abstract Research on spatial segregation has suggested that social mix may be a temporary phase in class displacement, where relations between different groups are at best divided or 'tectonic', for instance in England. Political and policy discourses, by contrast, tend to uncritically valorize social mix as a means to breaking up concentrations of poverty and providing neighbourhoods with a middle‐class voice. In the literature, little attention has been paid to power dynamics in socially mixed neighbourhoods and the implications this may have for understanding theory and policy. The five articles that make up this symposium address the ways in which social and ethnic groups interact in major cities in Europe and North America and, as the title suggests, this involves taking into account power relations, domination and negotiation between the different groups. There is a need to connect the experience of the deployment of power within neighbourhoods (and between them) with the discussions of power mechanisms at work in wider urban processes.